GUIDE-LINING FOR LEARNING TO OPTIMIZING LEARNING ACHIEVEMENT - Arif Efendi; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2019)
This study recognizes the role of variations in teaching in the learning process of third semester students in the Non-Formal Education STKIP Muhammadiyah Erekang. The problems of this study are: 1) What is the role of variations in teaching in the learning process of third semester students in the Non-Formal Education STKIP Muhammadiyah Erekang; 2) Whether through the role of variations in teaching in the learning process in Non Formal Education STKIP Muhammadiyah Erekang can improve student learning outcomes in the third semester. The research that will be used is descriptive research and reflects deeply on several aspects of teaching and learning activities. The focus of this research is to improve student learning outcomes in the subject of the role of variations in teaching in the third semester student learning process of the Non-Formal Education Study Program STKIP Muhammadiyah Enrekang. The research subjects were all students in the third semester of the Non-Formal Education STKIP Muhammadiyah Erekang with 75 students consisting of two classes namely class B totaling 35 and class A totaling 40. The instruments to be used were observation, tests and documentation. The data will be processed by percentage analysis and presented in the form of a description and presentation. The implementation plan begins by asking questions, thinking together and answering; 2) The application of the role of teaching variation in the third semester student learning process in the Non-Formal Education STKIP Muhammadiyah Erekang will improve student learning outcomes. The aims and objectives of education held in schools are non-formal education channels. The main target of education can be achieved well, it needs to begin with the concept of integration through the role of variations in teaching in the learning process of students.